Framdrivningssystem för LNG-tankfartyg - användning av gasturbin för elektrisk framdrivning - Moberg, Isabelle; Alfredsson, Jimmy (My University, 2014)
In this literature study, the advantages and disadvantages for gas turbine electric propulsion are compared with those for dual fuel diesel electric propulsion of LNG carriers. LNG is natural gas that has been liquefied to facilitate the transportation. The boiling off gas is used as primary fuel since it is more environmentally friendly than heavy fuel oil. The result show that the choice of prime mover for LNG carriers depends on i.a. degree of efficiency, fuel consumption, available cargo space and the reliability and availability of the systems. The ability to dispose the boil off gas is a central matter for the availability of the prime mover. Currently, there are no LNG carriers using gas turbine electric as a prime mover. The study however shows that gas turbine electric propulsion in combination with steam turbines has good qualifications to compete with the commercial propulsion systems; steam turbines and slow speed diesel engines with reliquefaction plant. Gas turbine electric propulsion in combination with a steam turbine is more beneficial than dual fuel diesel electric propulsion, since gas turbines are able to use the boil off gas at all running situations.
Keywords: Energi; Transport; Annan teknik; Energy; Transport; Other Engineering and Technologies